Histone deacetylase inhibitors block IFNγ-induced STAT1 phosphorylation - Ginter, Torsten; Hildebrand, Dagmar; Hieke-Kubatzky, Katharina (Cellular signalling, 2012)
Signal transducer and activator of transcription 1 (STAT1) is important for innate and adaptive immunity. Histone deacetylase inhibitors (HDACi) antagonize unbalanced immune functions causing chronic inflammation and cancer. Phosphorylation and acetylation regulate STAT1 and different IFNs induce phosphorylated STAT1 homo-/heterodimers, e.g. IFNα activates several STATs whereas IFNγ only induces phosphorylated STAT1 homodimers. In transformed cells HDACi trigger STAT1 acetylation linked to dephosphorylation by the phosphatase TCP45. It is unclear whether acetylation differentially affects STAT1 activated by IFNα or IFNγ, and if cellular responses to both cytokines depend on a phosphatase-dependent inactivation of acetylated STAT1. Here, we report that HDACi counteract IFN-induced phosphorylation of a critical tyrosine residue in the STAT1 C-terminus in primary cells and hematopoietic cells. STAT1 mutants mimicking a functionally inactive DNA binding domain (DBD) reveal that the number of acetylation-mimicking sites in STAT1 determines whether STAT1 is recruited to response elements after stimulation with IFNγ. Furthermore, we show that IFNα-induced STAT1 heterodimers carrying STAT1 molecules mimicking acetylation bind cognate DNA and provide innate anti-viral immunity. IFNγ-induced acetylated STAT1 homodimers are though inactive, suggesting that heterodimerization and complex formation can rescue STAT1 lacking a functional DBD. Apparently, the type of cytokine determines how acetylation affects the nuclear entry and DNA binding of STAT1. Our data contribute to a better understanding of STAT1 regulation by acetylation.
Gesehen am 27.06.2018